A 3D-Printed Do-It-Yourself ELISA Plate Reader as a Biosensor Tested on TNFα Assay - Pohanka, Miroslav; Keresteš, Ondřej; Žáková, Jitka (Biosensors, 2024)
Simple analytical devices suitable for the analysis of various biochemical and immunechemical markers are highly desirable and can provide laboratory diagnoses outside standard hospitals. This study focuses on constructing an easily reproducible do-it-yourself ELISA plate reader biosensor device, assembled from generally available and inexpensive parts. The colorimetric biosensor was based on standard 96-well microplates, 3D-printed parts, and a smartphone camera as a detector was utilized here as a tool to replace the ELISA method, and its function was illustrated in the assay of TNFα as a model immunochemical marker. The assay provided a limit of detection of 19 pg/mL when the B channel of the RGB color model was used for calibration. The assay was well correlated with the ELISA method, and no significant matrix effect was observed for standard biological samples or interference of proteins expected in a sample. The results of this study will inform the development of simple analytical devices easily reproducible by 3D printing and found on generally available electronics.
Keywords: kolorimetrie; biosensor; Printing, Three-Dimensional; Humans; Biosensing Techniques; enzyme-linked immunosorbent assay; inflammation; ELISA; lidé; biosenzitivní techniky; immunosensor; Enzyme-Linked Immunosorbent Assay; TNF-alfa; image; Colorimetry; colorimetry; 3D tisk; Tumor Necrosis Factor-alpha; cytokine